2021
DOI: 10.3390/ph14050403
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Pulmonary Damage and Peripheral Vascular Manifestations in Systemic Sclerosis Patients

Abstract: Systemic sclerosis (SSc) is an autoimmune disease, characterized by the presence of generalized vasculopathy and tissue fibrosis. Collagen vascular disorder in SSc is due to fibroblast and endothelial cell dysfunctions. This leads to collagen overproduction, vascular impairment and immune system abnormalities and, in the last stage, multi-organ damage. Thus, to avoid organ damage, which has a poor prognosis, all patients should be carefully evaluated and followed. This is particularly important in the initial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 20 publications
(35 citation statements)
references
References 123 publications
(373 reference statements)
0
34
0
1
Order By: Relevance
“…Before the advent of Computed Tomography scanning (CT), the identification of ILD was often a difficult task, even if early autopsy studies reported that up to 100% of patients had parenchymal involvement. Indeed, as many as 90% of SSc-ILD patients have interstitial abnormalities on high-resolution computed tomography (HRCT) and 40-75% have changes in pulmonary function tests (PFT) [19][20][21][22]. The clinical history of these patients usually reveals the insidious onset of exertional dyspnoea and a nonproductive cough.…”
Section: The Role Of Hrtc In Ssc-ildmentioning
confidence: 99%
See 1 more Smart Citation
“…Before the advent of Computed Tomography scanning (CT), the identification of ILD was often a difficult task, even if early autopsy studies reported that up to 100% of patients had parenchymal involvement. Indeed, as many as 90% of SSc-ILD patients have interstitial abnormalities on high-resolution computed tomography (HRCT) and 40-75% have changes in pulmonary function tests (PFT) [19][20][21][22]. The clinical history of these patients usually reveals the insidious onset of exertional dyspnoea and a nonproductive cough.…”
Section: The Role Of Hrtc In Ssc-ildmentioning
confidence: 99%
“…Considering the heterogeneity of SSc-ILD and the potential absence of symptoms, patients may be diagnosed earlier and more efficiently through a multidisciplinary evaluation and team collaboration [22][23][24][25][26][27][28][29]. Furthermore, it is prudent to consider as many parameters as possible to enhance clinical outcomes when assessing and monitoring newly diagnosed patients.…”
Section: Introductionmentioning
confidence: 99%
“…Lung vascular damage is mainly represented by PAH, a condition that plays an important role in SSc prognosis, as it is related to increased mortality [ 4 , 21 , 22 , 23 ]. Histologically, early pathologic lesions of PAH manifest with medial and intimal thickening, subsequent subintimal fibrosis in an onion-skin pattern and eventual reduplication of the internal elastic lamina [ 24 ], while later lesions comprise plexiform and “glomeruloid” nodules in small arteries with fibrin thrombi formation [ 24 ].…”
Section: Vascular Wall Alterations In Systemic Sclerosis and Related Clinical Manifestationsmentioning
confidence: 99%
“…Systemic sclerosis (SSc) is a connective tissue disease characterised by immune activation, vasculopathy and fibrosis [ 1 , 2 , 3 , 4 , 5 , 30 , 31 , 32 ]. The fibrosis and vasculopathy processes are strictly involved in the development of SSc-ILD [ 1 , 2 , 3 , 4 , 5 , 30 , 31 , 32 ].…”
Section: Systemic Sclerosis Associated Interstitial Lung Diseasementioning
confidence: 99%